2015
DOI: 10.1096/fasebj.29.1_supplement.282.7
|View full text |Cite
|
Sign up to set email alerts
|

F‐actin Binding Protein, Anillin, Regulates Integrity of Intercellular Junctions in Human Epithelial Cells

Abstract: Tight junctions (TJ) and adherens junctions (AJ) are key morphological features of differentiated epithelial cells that regulate the integrity and permeability of tissue barriers. Structure and remodeling of epithelial junctions depends on their interactions with the underlying actomyosin cytoskeleton. Anillin is a unique scaffolding protein interacting with different cytoskeletal components, including actin filaments and myosin motors. Its role in the regulation of mammalian epithelial junctions remains unexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Our study identifies ANLN as a major regulator of the actin cytoskeleton and epidermal morphogenesis. In keeping with previous reports [31,[34][35][36], we demonstrate that ANLN is essential for AJ organization in the developing epidermis and defects in the actin cytoskeleton can also explain abnormalities in apicobasal polarity and BM assembly [15], which are all major regulators of epidermal morphogenesis [3,80]. Moreover, we uncover an early, novel function for ANLN in mitotic rounding and its dependent processes: chromosome segregation, spindle orientation, and mitotic progression (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our study identifies ANLN as a major regulator of the actin cytoskeleton and epidermal morphogenesis. In keeping with previous reports [31,[34][35][36], we demonstrate that ANLN is essential for AJ organization in the developing epidermis and defects in the actin cytoskeleton can also explain abnormalities in apicobasal polarity and BM assembly [15], which are all major regulators of epidermal morphogenesis [3,80]. Moreover, we uncover an early, novel function for ANLN in mitotic rounding and its dependent processes: chromosome segregation, spindle orientation, and mitotic progression (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Because ANLN was recently shown to function in adherens junctions (AJs) [34,36], and because we detected ANLN also in epidermal junctions (Fig. 1A, B), we asked whether ANLN deficiency affects AJ organization.…”
Section: Adherens Junction Defects Are Followed By Polarity and Basem...mentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanosensitive ion channel, such as TRP (Transient Receptor Potential) and Piezo are additional potent transducers of physical information to the cell. Their activation in response to tensile forces applied to the cell membrane allows calcium to pass across a gradient into the cytoplasm activating signaling cascades that influence cell adhesion and keratinocyte differentiation 90,91 . Piezo1, a family member of the mechanosensitive cation channels, which is also expressed in epidermal keratinocytes, has previously been implicated in mediating keratinocyte mechanical sensitivity and migration during wound healing 92,93 .…”
Section: Discussionmentioning
confidence: 99%
“…The lack of obvious phenotype in initial myosin recruitment upon disruption of anillin may be due to functional redundancy, as suggested by studies in cultured cells (Piekny and Glotzer, 2008). In addition to a critical function in cytokinesis, recent studies have also revealed anillin’s function in regulating myosin localization at the cell-cell junctions (Wang et al, 2015) and organizing medial-apical actomyosin network in non-dividing epithelial cells (Arnold et al, 2019). Interestingly, a recent study suggests that anillin may function as an unconventional RhoA effector that feeds back and boosts RhoA’s activity by kinetically increasing its residence time at PI(4,5)P 2 -enriched membrane (Budnar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%